Based on bimetallic FeCo MOFs electrochemical sensor with a low detection limit for trace copper ions detection - Ruiying Zhu; Lifeng Ding; Qiang Li; Hongmei Dong; Mengjie Shi; Zhengwei Song; Shengling Li; Hao Chen; Jiahang Zhang (Results in Chemistry)
Environmental contamination by heavy metal ions poses significant health risks, emphasizing the urgent need for effective detection methods. In the work, it develops a bimetallic FeCo MOFs electrochemical sensor for trace copper ions detection in water, using a NaOH-mediated synthesis to modify MOFs materials. Iron ion doping introduces a bimetallic site, significantly enhancing the conductivity of the original ZIF-67. The addition of reduced graphene oxide (RGO) further improves conductivity due to its folded structure, which facilitates greater MOF deposition on the electrode surface. Additionally, the incorporation of Nafion enhances the stability of the MOF in aqueous environments. Sensitivity tests show effective detection of Cu2+ in the concentration range of 0.01–1 μM, with a LOD of 6.54 nM. And the sensor has exceptional stability, reproducibility, and interference resistance. The sensor demonstrated successful application in detecting Cu2+ in water samples, showing potential for broader applications in monitoring other heavy metal ions in environmental water samples.